PEOPLE MANAGEMENT IN THE TRANSITION TO SMART INDUSTRY - Cristina Silva, Gabrielle; Henrique de Oliveira Batista, Marcelo; Elaine Benetelli Geron, Regina (Revista Gênero e Interdisciplinaridade, 2025)
Industry 4.0 represents a milestone in the evolution of production processes and labor relations, characterized by the integration of advanced digital technologies such as artificial intelligence, the Internet of Things, big data, and automation. This technological transformation has profoundly impacted people management, requiring a reconfiguration of organizational, cultural, and human development strategies. The results indicate that factors such as organizational culture, transformational leadership, competency-based management, and reskilling and upskilling policies are essential to fostering innovative and collaborative environments. The importance of diversity, inclusion, and employee experience is also highlighted as key elements for business competitiveness in digital contexts. It is concluded that digital transformation requires a repositioning of the human resources sector, which must act as a mediator between technology and human capital, ensuring that technological changes are accompanied by sustainable human development aligned with contemporary market demands.